Lumberjanes. A bird's-eye view - Watters, Shannon; Leyh, Kat; Pietsch, Carey; Sotuyo, Ayme; Ellis, Grace; Stevenson, ND (Los Angeles, CA : BOOM! Box, a division of Boom Entertainment, Inc., 2017)
The High Council is coming to camp and counselor Jen is determined to make everything perfect, even though a storm is brewing and kittens from the boys' camp are manifesting magical powers. It's every Lumberjane on deck as the girls do their best to prep the grounds for inspection-- but there are some storms no one can prepare for.
"Originally published in single magazine form as Lumberjanes No. 25-28"--Title page verso.
Created by Shannon Watters, Grace Ellis, Noelle Stevenson & Brooke Allen--Page 5.
3.8
5-8
GN290L
Keywords: Teenage girls -- Comic books, strips, etc -- Juvenile fiction; Best friends -- Comic books, strips, etc -- Juvenile fiction; Friendship -- Comic books, strips, etc -- Juvenile fiction; Camps -- Comic books, strips, etc -- Juvenile fiction; Monsters -- Comic books, strips, etc -- Juvenile fiction; Teenage girls -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Camps -- Fiction; Monsters -- Fiction; Action and adventure comics; Horror comics; Graphic novels; Comics (Graphic works)